Efficacy of leukocyte-platelet-rich fibrin membrane in immediate postextraction implant placement: A randomized controlled trial - Monal Soni; Shalini Gugnani; Nymphea Pandit; Deepika Bali; Monia Sharma (Wolters Kluwer Medknow Publications, 2023)
Background: Leukocyte-platelet-rich fibrin (L-PRF) membrane is an emerging autologous healing biomaterial that promotes angiogenesis and healing in immediate implant sites. The purpose of the study was to evaluate hard and soft tissue outcomes of immediate implant placement with or without L-PRF. Materials and Methods: A total of 18 immediate implants were divided randomly into two groups of 9 implants each, i.e., Group 1 and Group 2. All sites received a definitive restoration after 3 months of implant placement and were followed up for a period of 6-months. Results: Addition of L-PRF in the extraction sockets when placing immediate implants resulted in statistically nonsignificant benefit in terms of clinical and radiographic parameters when compared to immediate implant placement without L-PRF. Conclusion: Immediate implant placement in Group 2 demonstrated marginal but statistically significant benefit as compared to sites in Group 1.